Medicinal Plants and Natural Products: More Effective and Safer Pharmacological Treatment for the Management of Obesity - Negi, Harsha; Gupta, Meenakshi; Walia, Ramanpreet; Khataibeh, Moayad; Sarwat, Maryam (Current Drug Metabolism, 2021)
Obesity is a major lifestyle disorder, and it is correlated with several ailments. The prevalence of obesity has elevated over the years, and it has become a global health problem. The drugs presently used for managing obesity have several side effects, such as diarrhea, leakage of oily stools, etc. On the contrary, herbal plants and natural products are considered safe for use because they have lesser side effects. New compounds isolated from medicinal plants are screened and identified to determine their effectiveness and potential in preventing abnormal weight gain. In this review, the medicinal plants and natural materials are surveyed across the literature to cover those that have the potential for managing and controlling weight gain. Furthermore, their mechanism of action, active components, and experimental methodologies are also reviewed. These herbal products can be developed as formulations for therapeutic use in obesity. The herbal plants mentioned in the review are classified based on their mechanism of action, inhibition of pancreatic lipase, and appetite suppression activities. The ability to inhibit pancreatic lipase enzyme has been used to determine the effectiveness of herbal products for the prevention of abnormal weight gain because of its action on dietary fat and suppression of appetite. This review is an attempt to summarize the herbal plants and natural products that can be used to develop formulations effective in controlling weight gain and obesity.
Keywords: weight gain